2001
DOI: 10.1001/archinte.161.2.272
|View full text |Cite
|
Sign up to set email alerts
|

Incident Thromboembolism in the Aorta and the Renal, Mesenteric, Pelvic, and Extremity Arteries After Discharge From the Hospital With a Diagnosis of Atrial Fibrillation

Abstract: A hospital diagnosis of AF is an important risk factor for peripheral arterial thromboembolic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0
11

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 30 publications
4
73
0
11
Order By: Relevance
“…Activated coagulation systems also cause mesenteric ischemia. In the Denmark study patients with peripheral arterial thromboembolism caused by atrial fibrillation occurred 29% in the mesenteric arteries, 2% in the renal artery and 61% in the extremities, and sometimes more than one site at the same time [6]. Generalized atherosclerosis is also major risk for acute mesenteric ischemia; Mishima Y reported 27% of 162 cases has general atheroma [7].…”
Section: Discussionmentioning
confidence: 99%
“…Activated coagulation systems also cause mesenteric ischemia. In the Denmark study patients with peripheral arterial thromboembolism caused by atrial fibrillation occurred 29% in the mesenteric arteries, 2% in the renal artery and 61% in the extremities, and sometimes more than one site at the same time [6]. Generalized atherosclerosis is also major risk for acute mesenteric ischemia; Mishima Y reported 27% of 162 cases has general atheroma [7].…”
Section: Discussionmentioning
confidence: 99%
“…Bu trombüslerin kaynağı çoğunlukla kardiyak kökenlidir ve 600 hastayı kapsayan bir çalışmada, kardiyak kökenli bu trombüslerin periferde en sık ekstremite arterleri (%61), mezenterik arterler (%29), pelvik arterler (%9), aorta (%7) ve renal arterlerde (%2) tromboemboliye neden oldukları görülmüştür. 7 Dolaşımdaki kolesterol embolileri ise genellikle çapı 150-200 mm olan küçük arterleri tıkamakta olup, bunun böbrekteki karşılığı arkuat, interlobüler ve terminal arterlerdir. 8 Teşhiste görüntüleme yöntemi olarak renal ultrasonografi, izotoplu renal sintigrafi, ekskretuvar ürografi, BT ve selektif renal anjiyografi kullanılabilir.…”
Section: Discussionunclassified
“…Frost L et al [9] followed 30,000 patients with atrial fibrillation over a 13-year period and noted 2% incidence of renal artery embolism. Hazanov N et al [6] reported 44 cases of ARI in patients with atrial fibrillation over 18-year period.…”
Section: Discussionmentioning
confidence: 99%